下一世代OFDM-based全光封包交換都會網路之技術與實現---總計畫 - 楊啟瑞; YUANG MARIA C. (My University, 2010)
隨著高容量寬頻固定式擷取網路與無線行動式擷取網路之出現，以及網際網路高頻寬需求與支援語音、視訊、數據、無線之quad-play服務需求日漸成長，未來趨勢將朝向全光網路科技，同時光纖傳輸無線電頻訊號(radio over fiber)技術已經引起廣大的興致。為了執行下世代無線通訊系統，正交分頻多工系統(OFDM)在現有主要多工技術上，被認為是最佳技術。這項事實使得未來下一世代全光網路設計與實現，OFDM在Layer-1成為經得起考驗之技術。本整合型研究計畫的目的即在於設計並建構原型OFDM全光都會網路，滿足下列三項重要目的。 首先，下一世代全光都會網路需要全光封包交換(OPS)技術來保證有效率且細緻的頻寬分配與各類型服務品質保證(QoS)以支援Quad-play，OPS之挑戰可以藉由幾種方法來實現，其中混合式OFDMA/WDM存取機制被認為是最具前瞻性的OPS技術，本計畫首要目標就在設計建構原型OFDMA/WDM存取機制以滿足上述要求。第二目的在於大多數OFDM相關研究強調在遠距離傳輸之應用或者無線環境設定下之光載電頻(RoF)系統，本計畫第二目標則是設計適用於全光都會網路之高頻譜效率OFDM傳輸系統，並可擴充至光載電頻之運用。第三目的則是當上述OFDM系統即將實現時，大多數的研究者受制於光學OFDM系統高輸出計算能力而採用模擬方式來驗證，我們最後的目標即是透過硬體架構設計來實現光學OFDM傳輸系統。 本整合型研究計畫（楊啟瑞教授主持），旨在探討下一世代支援Quad-play應用服務之OFDM全光封包交換都會網路技術與實現，其由四項子計畫組合而成。就一般性而言，第一個子計畫專心致志於Layer-2/3之技術；第二與第三子計畫研究Layer-1之OFDM傳輸與通訊技術，而最後一個子計畫則專注於IC/FPGA架構設計，並且將其他子計畫設計之系統實現。如圖11-1，子計畫一（楊啟瑞教授主持）將對全光都會WDM環狀網路之OFDMA/WDM媒介存取控制與頻寬分配系統進行設計、分析，並建構雛形研究平台；子計畫二（馮開明教授主持）目標在發展與實作適用於都會網路應用之高頻譜效率與可重新置換OFDM傳輸技術；子計畫三（陳智弘教授主持）研究四倍頻光電調變技術以整合OFDM與光載電頻訊號系統，以支援quad-play服務；子計畫四（黃元豪教授主持）主要針對光學OFDM傳輸所需之基頻處理器進行設計與實現。透過四個子計畫之緊密合作，從第一年第三季至這三年期計畫結束為止，我們將著手架構以IC/FPGA為基礎之雛形實驗平台。

With the emergence of both high capacity broadband fixed and mobile wireless access networks, and the ever-growing demand for high Internet bandwidth and support of quad-play (i.e., video, voice, data, and wireless), the future trend toward optical networking and optical transport of radio frequency signals, referred to radio over fiber, has attracted great interest. For implementing the next-generation wireless communication systems, OFDM systems have been considered the most promising technology among prevailing candidates. Such fact makes OFDM a future-proof underlying Layer-1 technology for the design and implementation of next-generation optical networks. The major goal of the integrated project is to design and prototype an OFDM-based optical metro network satisfying three following prominent objectives. First, next-generation optical metro networks require the Optical Packet Switching (OPS) technique to ensure efficient and fine-grained bandwidth allocation and various Quality-of-Service (QoS) guarantees for supporting quad-play. Such OPS challenge can be realized via several approaches in which the hybrid OFDMA/WDM access mechanism has been considered the most promising OPS technology. Our first goal of the project is to design/prototype an OFDMA/WDM access scheme satisfying the above requirements. Second, most OFDM-related work emphasizes its applications for long-haul transmission or radio over fiber (RoF) systems particularly under the wireless setting. Our second goal of the project is to design a highly spectral-efficient OFDM transmission system with and without the augmentation of the RoF, particularly for optical metro networks. Finally, when it comes down to the realization of such OFDM-based systems, most of the work has been justified via simulation due to stringent requirements of high-throughput computation capability for optical OFDM systems. To this end, our final goal of the project is to realize the optical OFDM transmission systems through the hardware architectural design. The main objective of this integrated project (PI: Prof. Maria C. Yuang) is the provision of the technologies and realization of next-generation OFDM-based optical packet-switched metro networks supporting quad-play applications. The integrated project consists of four subprojects. In general, the first subproject is devoted to the layer-2/3 technologies; the second and third subprojects research the layer-1 OFDM transmission and communication technologies; and the last subproject focuses on the IC/FPGA architectural design and implementation techniques of systems designed by other subprojects. In particular, as shown in Figure 11-2, Subproject 1 (PI: Prof. Maria C. Yuang) is responsible for the design, analyses, and prototyping of OFDMA/WDM medium access control and bandwidth allocation system for optical metro WDM ring networks; Subproject 2 (PI: Prof. Kai-Ming Feng) aims at the development and implementation of a highly re-configurable OFDM transmission technology for metro-area network applications with high spectral efficiency; Subproject 3 (PI: Prof. Jyehong Chen) concentrates on the combination of OFDM and RoF systems via a frequency quadrupling approach to support quad-play services; Subproject 4 (PI: Prof. Yuan-Hao Huang) focuses on the design and implementation of baseband processor for optical OFDM transmission systems. Through the tight collaboration of four subprojects, we undertake the construction of the IC/FPGA-based prototyping network from the third quarter of the first year to the end of the three-year project.
Technologies and Realization of Next-Generation OFDM-Based Optical Packet-Switched Metro Networks
Keywords: 正交分頻多工(OFDM); 正交分頻多重存取(OFDMA); 分波多工(WDM); 都會型網路(MAN); 光線路交換(OCS); 光群聚交換(OBS); 光封包交換(OPS); 服務品質保證(QoS); 媒介存取控制(MAC); 頻寬分配; Quad-Play四合一服務; 光纖通訊; 信號調變; 光學塞取多工(OADM); 光載電頻訊號(RoF); 光纖到家(FTTH); 微波光學; 多重載波傳輸; 多路徑效應; 基頻訊號處理; 通道等化器; 符元間干擾(ISI); 快速傅立葉轉換器; 可程式邏輯匣陣列; 積體電路(IC); 多相位濾波器; Orthogonal Frequency Division Multiplexing (OFDM); Orthogonal Frequency Division Multiple Access (OFDMA); Wavelength Division Multiplexing (WDM); Metropolitan Area Network (MAN); Optical Circuit Switching (OCS); Optical Burst Switching (OBS); Optical Packet Switching (OPS); Quality-of-Service (QoS); Medium Access Control (MAC); Bandwidth Allocation; Quad-Play; Optical Fiber Communications; Modulation Format; Optical Add/Drop Multiplexing (OADM); Radio-over-Fiber (RoF); Fiber to the Home (FTTH); Microwave Photonics; Multi-Carrier Transmission; Multi-path Effect; Baseband Processing; Channel Equalizer; Inter-Symbol Interference (ISI); Fast Fourier Transform Processor; Field Programmable Gate Array; Integrated Circuit (IC); Polyphase-Filter; Multi-phase Butterfly Processor